Global advancements in BIM-based building e-permit system adoption: a review - Sun, Hongwei; Kim, Inhan (Journal of Civil Engineering and Management, 2026)
Globally, several countries have begun to promote the application of building information modeling (BIM) technology and implement BIM-based building e-Permit systems. Despite the relatively rapid updates in the field of BIM-based building e-Permit systems, currently a lack of systematic sorting and summarization exists. This review evaluates the situation of seven representative countries from three aspects: the current adoption status of the BIM-based building e-Permit system, adoption background (BIM-related policy, roadmap, standards, and guidelines), and a future development plan for digital construction. These three aspects are analyzed, common measures across these countries are summarized. Four viewpoints are extracted for promoting BIM-based building e-Permit system adoption, which are mandatory policy orientation, standardization, internationalization, and intelligence. Finally, as the integration of AI into BIM-based building e-Permit systems is a recent research trend, this study also investigates existing research, highlights bottlenecks and points out future directions for AI integration.